An avulsed radial artery with a high take-off. (April 2015) - Rojas-Marte, Geurys; Chen, On; Verma, Shivani; Rao, Atul; Shani, Jacob; Ayzenberg, Sergey
A 63-year-old female was diagnosed with severe aortic stenosis, who underwent a diagnostic coronary angiography via transradial approach prior an aortic-valve replacement. After imaging the left coronary system, entrapment of the diagnostic catheter was encountered as a result of spasm of the radial artery. An arteriogram of the arm revealed an anatomical variation in the radial artery (high take-off). Several attempts to remove the entrapped catheter resulted in avulsion of the artery, which was managed successfully with coil embolization. To our knowledge, no such complication has been reported.